(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The project Práticas performativas para perceber e responder ao Antropoceno no ensino fundamental was carried out as an internship in the ninth grade at João Gonçalves School in Florianópolis in 2023. It used Ana Mae Barbosa’s (2012) triangular conception of art education as its methodology and, based on the experience of Francis Alÿs’s performance Paradox of Praxis 1, developed three performative programs (Fabião, 2013): Chut-ação de gelo, Dança com gelo e Cartazes do gelo. Based on the report of these activities, I comment on the potential and problems of recreating performances in school, as well as how to reconcile the transgression inherent in performance practice with the rules of the school environment.